The impact of concurrent training and antioxidant supplementation on the factors associated with the ocular lens opacity in diabetic rats. (2nd January 2022) - Amirahmadi, Mousa; Salesi, Mohsen; Yousefi, Reza; Daryanosh, Farhad; Nemati, Javad; Kurganov, Boris I.
Abstract: The current study was aimed to investigate the protective effect of vitamins C and E (VCE) supplementation, exercise, and their concurrent application against cataract incidence in the diabetic rats. The obtained results indicated that different supplementation and training treatments were capable to preserve the lens transparency in the diabetic rats. Also, upon applying different supplementation and training treatments, the level of glutathione (GSH) and activity of antioxidant enzymes in the diabetic rats was preserved approximately close to their control levels. In addition, different treatments were capable to maintain the structural integrity of the lens proteins in diabetic rats. Moreover, VCE supplementation, exercise and their simultaneous application prevented lens crystallins of diabetic rats against fibrillation and formation of the increased oligomeric sizes. The results of this study signify the importance of antioxidant supplementation and exercise in reducing the detrimental effects of hyperglycemia on the eye lenses.